2019
DOI: 10.3390/bs9030028
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time Improvements by Neural Bistability

Abstract: The often reported reduction of Reaction Time (RT) by Vision Training) is successfully replicated by 81 athletes across sports. This enabled us to achieve a mean reduction of RTs for athletes eye-hand coordination of more than 10%, with high statistical significance. We explain how such an observed effect of Sensorimotor systems’ plasticity causing reduced RT can last in practice for multiple days and even weeks in subjects, via a proof of principle. Its mathematical neural model can be forced outside a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 97 publications
3
10
0
Order By: Relevance
“…Visuo-spatial-motor training is nowadays ubiquitous in enhancing athletes’ abilities [ 105 ]. The asset of visuo-spatial-motor training is: shutting down the view has the effect of saccades performing slightly poorer, which increases the saccade size [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visuo-spatial-motor training is nowadays ubiquitous in enhancing athletes’ abilities [ 105 ]. The asset of visuo-spatial-motor training is: shutting down the view has the effect of saccades performing slightly poorer, which increases the saccade size [ 227 ].…”
Section: Discussionmentioning
confidence: 99%
“…The visuo-spatial-motor-motor intervention in this research was performed upon invitation by the sport training expert (GS), because of his expertise in such training for athletes [ 105 ]. The research into effectivity of this renovated training program took place in 2019 and comprised of three groups: An observational control group, a group of trained by physical therapy (named the ‘motor group’), and a group trained by physical therapy + visuo-spatial-motor training (named the ‘visuo-motor group’).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the midpoint of the NDR segment for the F pw (G) function is shifted to the origin, and it corresponds to the best approximation of the F pw (G) function using cubic nonlinearity F q (G). Based on Equation 11, the inductive current IL models the behavior of the membrane potential G, and the voltage on the capacitor U0 reflects the slow recovery potential W. The input signal Uin(t) is analogous to the input current Iext (t) of the neuron in Equations (6) and 7. Based on Equation (11), the inductive current I L models the behavior of the membrane potential G, and the voltage on the capacitor U 0 reflects the slow recovery potential W. The input signal U in (t) is analogous to the input current I ext (t) of the neuron in Equations (6) and (7).…”
Section: Fitzhugh-nagumo Model Based On a Current-controlled Switchinmentioning
confidence: 99%
“…These studies indicated that visual function is better among athletes than among non-athletes and that highly skilled athletes have better visual function than lower-skilled athletes 5 7 . Other studies have reported that these visual functions could be improved through training 7 , 9 , 16 20 .…”
Section: Introductionmentioning
confidence: 96%